2012
DOI: 10.4018/jeis.2012070104
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid MCDM Approach for Solving the ERP System Selection Problem with Application to Steel Industry

Abstract: Selecting a proper system of Enterprise Resource Planning (ERP) is a major challenge for enterprise managers. Heavy expenses of incorrect decisions in selection of ERP systems have made academics and managers consider this phase as highly important. Several research studies proposed different approaches to selecting the ERP and many case studies of organizational experiences have been published. However, there has been less regard for simultaneous use of the findings of academic studies and judgments of indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Gürbüz et al (2012) suggested an assessment framework using an integration approach that utilizes ANP, Choquet integral and Measuring Attractiveness by a Categorical Based Evaluation Technique for the evaluation of four ERP software alternatives. Jafarnejad et al (2012) investigated an integrated approach which includes Shannon entropy technique, DEMATEL, fuzzy AHP. Kara and Cheikhrouhou (2014) determined a two phase methodology, fuzzy AHP for criteria weights and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) for ranking the alternatives, to select the collaborative software.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…Gürbüz et al (2012) suggested an assessment framework using an integration approach that utilizes ANP, Choquet integral and Measuring Attractiveness by a Categorical Based Evaluation Technique for the evaluation of four ERP software alternatives. Jafarnejad et al (2012) investigated an integrated approach which includes Shannon entropy technique, DEMATEL, fuzzy AHP. Kara and Cheikhrouhou (2014) determined a two phase methodology, fuzzy AHP for criteria weights and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) for ranking the alternatives, to select the collaborative software.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…Temur and Bolat [19] showed that the ERP system selection problem area has high sensitivity to the uncertain environment, and decision makers should not undervalue the unsteadiness of criteria during the ERP system selection process, especially within volatile economies. Jafarnejad et al [20] proposed a MCDM Model including the DEMATEL technique and fuzzy AHP technique for solving the ERP system selection problem with application to the steel industry. In this study, the most important criteria in ERP selection were identified using the Shannon entropy technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ERP selection critical success factors have been vastly addressed and analyzed in ERP literature by many researchers (Kazemi et al, (2014); Jafarnejad et al, (2012); GüRbüZ et al, (2012); the assessment framework is constructed. The fuzzy analytic hierarchy process is then used for this framework (Figure 6).…”
Section: Selection Criteria and Hierarchy Establishmentmentioning
confidence: 99%